Chlorella sorokiniana Extract Prevents Cisplatin-Induced Myelotoxicity In Vitro and In Vivo - Perng, Ming-Der; Wen, Shu-Fang; Pan, I-Horng; Chao, Ya-Hsuan; Wu, Hsin-Chieh; Chang, Chih-Hsuan; Lin, Ni-Hsuan; Chuang, Kai-An; Li, Ming-Han; Lin, Shyh-Horng; Lin, Chi-Chen (Oxidative medicine and cellular longevity, 2020)
Cisplatin chemotherapy causes myelosuppression and often limits treatment duration and dose escalation in patients. Novel approaches to circumvent or lessen myelotoxicity may improve clinical outcome and quality of life in these patients. Chlorella sorokiniana (CS) is a freshwater unicellular green alga and exhibits encouraging efficacy in immunomodulation and anticancer in preclinical studies. However, the efficacy of CS on chemoprotection remains unclear. We report here, for the first time, that CS extract (CSE) could protect normal myeloid cells and PBMCs from cisplatin toxicity. Also, cisplatin-induced apoptosis in HL-60 cells was rescued through reservation of mitochondrial function, inhibition of cytochrome c release to cytosol, and suppression of caspase and PARP activation. Intriguingly, cotreatment of CSE attenuated cisplatin-evoked hypocellularity of bone marrow in mice. Furthermore, we observed the enhancement of CSF-GM activity in bone marrow and spleen in mice administered CSE and cisplatin, along with increased CD11b levels in spleen. In conclusion, we uncovered a novel mechanism of CSE on myeloprotection, whereby potentially supports the use of CSE as a chemoprotector against cisplatin-induced bone marrow toxicity. Further clinical investigation of CSE in combination with cisplatin is warranted.